DINAMIKA MAKNA HIJAB: Antara Kesalehan Personal dan Industri Fashion Global - Alina, Aurellia Iva; Sa’adah, Nayla Mu’linatus; Niswah, Arina Zaenan; 'Ubudiyah, Farikhatul (INSTITUT AGAMA ISLAM NEGERI PONTIANAK, 2025)
The use of hijab in the modern era has experienced a shift in meaning, from being a shar'i obligation to being part of a fashion trend and lifestyle expression. Social media and the fashion industry have made hijab a commodity that is influenced by aesthetics, social status, and popular culture, rather than solely by religious motivations. Many women wear hijab to look fashionable or because of environmental demands, rather than as a form of obedience to Allah. Therefore, the purpose of this research is to analyze the shifting meaning of hijab from a symbol of sharia observance to a commodity in the contemporary fashion industry, as well as the impact of social media in shaping the construction of the meaning of hijab for the Muslim generation. This research uses a qualitative library research method, with secondary data collected from various relevant literatures. These sources include scientific journals, academic books, and verses of the Qur'an. The results of the study can be seen that the use of hijab in the modern era has experienced a shift in meaning from syar'i obligations to fashion trends, so that it often loses its spiritual value and emphasizes aesthetic aspects and social status. Therefore, it is necessary to reorient the meaning of hijab based on tawhid so that its use becomes a form of servitude to Allah, not just an expression of external appearance.Penggunaan hijab di era modern telah mengalami pergeseran makna, dari yang awalnya merupakan kewajiban syar’i menjadi bagian dari tren fashion dan ekspresi gaya hidup. Media sosial dan industri fashion telah menjadikan hijab sebagai komoditas yang dipengaruhi oleh estetika, status sosial, dan budaya populer, bukan semata-mata karena motivasi religius. Banyak perempuan mengenakan hijab untuk tampil modis atau karena tuntutan lingkungan, selain sebagai bentuk ketaatan kepada Allah. Oleh karena itu, tujuan penelitian ini adalah untuk menganalisis pergeseran makna hijab dari simbol ketaatan syariat menjadi komoditas dalam industri fashion kontemporer, serta dampak media sosial dalam membentuk konstruksi makna hijab bagi generasi muslim. Penelitian ini menggunakan metode library research (studi pustaka) yang bersifat kualitatif, dengan data sekunder yang dikumpulkan dari berbagai literatur yang relevan. Sumber-sumber tersebut meliputi jurnal ilmiah, buku-buku akademik, serta ayat-ayat Al-Qur’an. Hasil penelitian dapat diketahui bahwa penggunaan hijab di era modern telah mengalami pergeseran makna dari kewajiban syar’i menjadi tren busana, sehingga seringkali kehilangan nilai spiritualnya dan lebih menonjolkan aspek estetika serta status sosial. Oleh karena itu, perlu adanya reorientasi makna hijab berdasarkan tauhid agar penggunaannya kembali menjadi wujud penghambaan kepada Allah, bukan sekadar ekspresi penampilan luar.